Indeks Persepsi Masyarakat Lingkar Tambang terhadap Upaya Reklamasi oleh PT. Amman Mineral Kaitannya dalam Kualitas Air - Azis, Abdul (BIOMARAS : Journal of Life Science and Technology, 2026)
Mining activities have the potential to affect land and water quality, making reclamation and environmental management the responsibility of companies. This study aims to analyze community perceptions of the success of land reclamation and water quality management by PT Amman Mineral Nusa Tenggara. The study used a quantitative descriptive method with a semi-structured approach to 150 respondents in Pasir Putih Village, Maluk Village, and Bukit Damai Village. Data were collected through a Likert scale questionnaire and analyzed using a community perception index, supported by water quality data based on pH, Total Dissolved Solids, and salinity parameters. The results showed that community perceptions of land reclamation were in the good to very good category, with the highest index value in Bukit Damai Village at 82.32%, followed by Pasir Putih Village at 74.64% and Maluk Village at 66.32%. Public perception of water quality management was in the adequate category, with an index value of 64.80% in Pasir Putih Village, 55.92% in Maluk Village, and 59.20% in Bukit Damai Village. Water quality measurements show that pH, TDS, and salinity parameters still meet clean water quality standards. The difference between technical results and public perception highlights the importance of improving transparency, communication, and community involvement in mining environmental management.